Implementation of Super Encryption Using Affine Cipher, Playfair Cipher, and RSA on Image Files - Arif, Muhamad; Achmad Fauzi; Hermansyah Sembiring (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
This research aims to enhance the security of image files by implementing a super-encryption technique that integrates three cryptographic algorithms from both classical and modern domains: Affine Cipher, Playfair Cipher, and RSA. Each algorithm provides a distinct layer of encryption applied sequentially—starting with byte-value transformation using the Affine Cipher, followed by byte-pair substitution through the Playfair Cipher, and concluding with public-key RSA encryption. The proposed approach was evaluated on image files while ensuring both integrity and byte-level equivalence between the original and decrypted files. The implementation was developed as a desktop application in Visual Basic .NET, featuring separate modules for encryption and decryption, along with structured displays of results and process logs. Experimental results indicate that this super-encryption method successfully preserves file integrity and significantly increases cryptographic complexity without altering file size. System security is substantially improved, as the combined algorithms make the encrypted data highly resistant to analysis without complete knowledge of the underlying structure and encryption keys. This approach offers a viable alternative for securing sensitive image files, such as identity documents and medical records.